Bencana, Informasi dan Keterlibatan Media - Nunung Prajarto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2008)
This article describes the role and involvement of media in reporting disaster. Media involvement in giving people information on disaster should based on human safety, security and dignity. This paper suggests that media report on pre, during and after a disaster should consider human values at the first priority.